The Neural Correlates of Consciousness and Attention: Two Sister Processes of the Brain - Nani, Andrea; Manuello, Jordi; Mancuso, Lorenzo; Liloia, Donato; Costa, Tommaso; Cauda, Franco (Frontiers in Neuroscience, 2019)
During the last three decades our understanding of the brain processes underlying consciousness and attention has significantly improved, mainly because of the advances in functional neuroimaging techniques. Still, caution is needed for the correct interpretation of these empirical findings, as both research and theoretical proposals are hampered by a number of conceptual difficulties. We review some of the most significant theoretical issues concerning the concepts of consciousness and attention in the neuroscientific literature, and put forward the implications of these reflections for a coherent model of the neural correlates of these brain functions. Even though consciousness and attention have an overlapping pattern of neural activity, they should be considered as essentially separate brain processes. The contents of phenomenal consciousness are supposed to be associated with the activity of multiple synchronized networks in the temporo-parietal-occipital areas. Only subsequently, attention, supported by fronto-parietal networks, enters the process of consciousness to provide focal awareness of specific features of reality.The Neural Correlates of Consciousness and Attention: Two Sister Processes of the Brain